2019
DOI: 10.2147/ceg.s195714
|View full text |Cite
|
Sign up to set email alerts
|

<p>Early Diagnosis And Management Of Malignant Distal Biliary Obstruction: A Review On Current Recommendations And Guidelines</p>

Abstract: Malignant biliary obstruction is a challenging condition, requiring a multimodal approach for both diagnosis and treatment. Pancreatic adenocarcinoma and cholangiocarcinoma are the leading causes of malignant distal biliary obstruction. Early diagnosis is difficult to establish as biliary obstruction can be the first presentation of the underlying disease, which can already be at an advanced stage. Consequently, the majority of patients (70%) with malignant distal biliary obstruction are unresectable at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 148 publications
(199 reference statements)
0
44
0
1
Order By: Relevance
“…In addition, we do not provide a systematic comparison between different approaches to the diagnosis of pancreatobiliary malignancies. About 70% of patients with pancreatic cancer present with inoperable malignant biliary strictures requiring biliary drainage in order to improve quality of life and to allow for palliative chemotherapy treatment [36,37]. However, not all patients with pancreatobiliary cancers require therapeutic interventions for biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we do not provide a systematic comparison between different approaches to the diagnosis of pancreatobiliary malignancies. About 70% of patients with pancreatic cancer present with inoperable malignant biliary strictures requiring biliary drainage in order to improve quality of life and to allow for palliative chemotherapy treatment [36,37]. However, not all patients with pancreatobiliary cancers require therapeutic interventions for biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Given the results of our study, we supposed that HCMS stents are the best choice in this group of patients due to the inherent advantages of both types of its characteristics. However, early occlusions of the HCMS and FCMS were noticed due to tumor overgrowth, and these finding were surprising and controversial, when compared with other studies[ 15 , 20 , 23 , 30 - 34 ]. Conio et al[ 20 ] have explained that this overgrowth may be due to a created tissue hyperplasia induced by inflammatory reaction caused by the membrane covering of the stents rather than a true tumor overgrowth.…”
Section: Discussionmentioning
confidence: 81%
“…Probably in these trials, the endoscopists used stents with an anti-migration system consisting of a portion of uncovered flares at both ends[ 24 ]. However, Yang et al[ 15 ] found no clinical usefulness of the anti-migration design[ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical bypass does seem to be superior in avoiding recurrent jaundice. The decision to perform endoscopic stent placement versus surgical bypass should be considered carefully, with the risks and benefits of each procedure discussed thoroughly with patients [9,10].…”
Section: Endoscopic Management Of Unresectable Malignant Biliary Strimentioning
confidence: 99%